Адсорбція іонів важких металів на штучних та природних сорбентах - Рогов, Володимир; Регуш, Андрій (Видавництво Національного університету «Львівська політехніка», 2001)
In the paper experimental results of the heavy metals ions removing on the birch activated carbon and on the nature ceolit in the range of small concentrations are presented. The mathematical description of the adsorbtion izoterms by means of extended Langmuir model is proposed. Results of the investigation may be used for the design of the adsorbtion plants, which clarifies seweges with small concentrations of the heavy metals ions.